Bipolar bozukluğun farklı dönemlerinde serum nörofilament hafif zincir, serum oligoklonal band ve inflamatuar belirteç düzeylerinin bilişsel işlevlerle ilişkisi / Relationship of serum neurofilament light chain, serum oligoclonal band and inflammatory marker levels with cognitive functions in different periods of bipolar disorder - TANGILNTIZ, Aise (My University, 2021)
Introduction: In our study, we aimed to investigate the levels of neuroinflammatory and neurodegenerative parameters (neurofilament light chain (NfL), serum oligoclonal band (OCB), intracellular cytokines (TNF-α, IL-1β, IL-6)) change in different stages of the disease in patients diagnosed with bipolar disorder and to evaluate the relationship between these neurobiological parameters and executive functions. Method: Our study was planned as a prospective paired case-control study. A total of 76 participants, 46 of whom were diagnosed with bipolar disorder according to DSM-5 criteria (16 in depression, 15 in hypomania, 15 in remission period) and admitted to the Psychiatry Outpatient Clinic of Bezmialem Vakıf University Medical Faculty Hospital between October 2019 and January 2021 and 30 healthy controls were included. Young Mania Rating Scale (YMRS) and Hamilton Depression Rating Scales (HDRS) were administered to all participants in the study. The clinical interviews, scales and neurocognitive tests were applied, and then blood was drawn to measure neuroinflammation-related parameters (NfL, OCB, intracellular cytokines (TNF-α, IL-1β, IL-6). Executive functions were examined via the Wisconsin card sorting test (WCST) and Stroop tests, and the relationship between these neurobiological parameters in different disease periods and executive functions were evaluated. Results: In our study, proinflammatory markers such as IL-1β, IL-6, TNF-α and NfL, OCB levels were found to be significantly higher in patients with bipolar disorder than in the control group (p<.001). No statistically significant difference was found in IL-1β, IL-6, TNF-α, NfL and OCB levels between patients in depression, hypomania and remission phase of bipolar disorder (p>0.05). In all these groups, there was a statistically significant prolongation of the total completion times in all sub-categories of the Stroop test with respect to healthy controls. The prolongation of stroop 2, stroop 3 and stroop 4 completion times correlated with increasing age (respectively; p=.029, p=.045, p=.011). It was determined that as the age of onset of the disease increased, the completion times of stroop 2 and stroop 5 lengthened. Apart from these findings, no statistically significant relationship was found between the duration of the disease, the number of mood episodes during the disease and the stroop test scores. When the WCMT total correct numbers analysed, it was determined that the patients in depression and the patients in remission performed significantly worse than the control group (p=.012, p=.015). Patients in depression period performed significantly worse than the control group in the number of completed categories of WCST (p=.001). When the number of depressive episodes increased, the patient's repetitive response level increased, but this was not statistically significant (p=.061). As IL-6 level decreased, it was determined that stroop 1, stroop 2 and stroop 5 completion times were impaired (p<0.05). No statistically significant relationship was observed between IL-1β, TNF-α, NfL and OCB levels and the stroop test scores. There was a negative correlation between IL-1β level and the completed first category on WCST. No statistically significant relationship was found between other biochemical parameters and WCST subcategories. A statistically significant difference was found in all subcategories, except for the stroop test and the total number of WCST errors in patients using only lithium, only valproic acid, and only antipsychotics (p<0.05). In post-hoc comparisons, a statistically significant prolongation was found in the total duration of stroop 1 and total time of stroop 3 in patients using only antipsychotics, and in the number of completed categories of WCST in patients using antipsychotics and valproic acid, compared to the control group. Conclusion: These findings from our study show that intracellular cytokines, NfL and OCB levels are higher in patients with bipolar disorder than in healthy controls. In addition, it was determined that patients with bipolar disorder have impaired executive functions compared to the healthy controls. IL-6 and IL-1β levels were associated with deterioration in cognitive functions. From this point of view, the level of these biochemical parameters can help us to evaluate the cognitive functions of patients diagnosed with bipolar disorder. We think that further studies are needed in larger samples on this subject. Keywords: Bipolar disorder, neuroinflamation, neurodegeneration, cognitive functions
Relationship of serum neurofilament light chain, serum oligoclonal band and inflammatory marker levels with cognitive functions in different periods of bipolar disorder
Giriş: Çalışmamızda bipolar bozukluk tanısı almış hastalarda nöroinflamatuar ve nörodejeneratif parametrelerin (nörofilament hafif zincir (NfL), serum oligoklonal band (OKB), hücre içi sitokinler (TNF-α, IL-1β, IL-6)) hastalığın farklı dönemlerindeki düzeylerinin ve bu nörobiyolojik parametreler ile yürütücü işlevler arasındaki ilişkinin değerlendirilmesi amaçlanmıştır. Yöntem: Çalışmamız prospektif eşleştirilmiş vaka-kontrol çalışması olarak planlanmıştır. Ekim 2019- Ocak 2021 tarihleri arasında Bezmialem Vakıf Üniversitesi Tıp Fakültesi Hastanesi Psikiyatri polikliniğine başvuran, DSM-5 kriterlerine göre Bipolar Bozukluk tanısı konulmuş 46 hasta (16 depresyon, 15 hipomani, 15 remisyon) ve 30 sağlıklı kontrol olmak üzere toplam 76 katılımcı dahil edilmiştir. Çalışmadaki tüm katılımcılara Young Mani Derecelendirme Ölçeği (YMDÖ) ve Hamilton Depresyon Derecelendirme Ölçekleri (HDDÖ) uygulanmıştır. Hastalarla klinik görüşme yapılmış, ölçekler ve nörobilişsel testler uygulanmış ve sonrasında nöroinflamasyonla ilişkili parametreleri (NfL, OKB, hücre içi sitokinler (TNF-α, IL-1β, IL-6)) ölçmek için kan alınmıştır. Yürütücü işlevler Wisconsin kart eşleme testi (WKET) ve Stroop testleri ile incelenmiş, nörobiyolojik parametrelerin hastalık dönemleri ve yürütücü işlevler ile ilişkisi değerlendirilmiştir. Bulgular: Çalışmamızda IL-1β, IL-6, TNF-α gibi proinflamatuar belirteçlerin ve NfL, OKB düzeylerinin bipolar bozukluk hasta grubunda, kontrol grubuna göre anlamlı olarak daha yüksek olduğu saptanmıştır (p<.001). IL-1β, IL-6, TNF-α, NfL ve OKB düzeylerinde bipolar bozukluğun farklı dönemlerindeki alt gruplarında istatistiksel olarak anlamlı bir fark saptanmamıştır (p>0.05). BB grupları kontrollerle karşılaştırıldığında, stroop testi tüm alt kategorilerinde toplam tamamlama sürelerinde istatistiksel olarak anlamlılık gösterecek düzeyde uzama mevcuttu. Yaş artışı ile stroop 2, stroop 3 ve stroop 4 tamamlama sürelerinin uzamasının istatistiksel olarak anlamlı düzeyde daha yüksek olması (sırasıyla; p=.029, p=.045, p=.011) ve hastalığın başlangıç yaşı arttıkça stroop 2 ve stroop 5 tamamlanma sürelerinin uzaması dışında (p=.039, p=.042) hastalık süresi, hastalık süresince geçirilen atak sayısı ile stroop testi arasında istatistiksel olarak anlamlı bir ilişki tespit edilmedi. WKET toplam doğru sayısı değerlendirildiğinde hem depresyondaki hem remisyondaki hastaların, kontrol grubuna göre anlamlı düzeyde daha kötü performans gösterdikleri belirlendi (p=.012, p=.015). WKET tamamlanan kategori sayısında depresyondaki hastaların kontrol grubuna göre anlamlı düzeyde daha kötü performans gösterdikleri saptandı (p=.001). Geçirilen depresif atak sayısı arttıkça hastaların yineleyici tepki düzeyinde artış olduğu tespit edildi ancak istatistiksel olarak anlamlı değildi (p=.061). IL-6 düzeyi azaldıkça stroop 1, stroop 2 ve stroop 5 tamamlanma sürelerinde bozulma olduğu belirlendi (p<0.05). IL-1β, TNF-α, NfL ve OKB düzeyleri ile stroop testi arasında istatistiksel olarak anlamlı bir fark gözlenmedi. IL-1β düzeyi ile WKET 1. kategoriyi tamamlama arasında negatif korelasyon mevcuttu. Diğer biyokimyasal parametreler ve WKET alt kategorileri arasında istatistiksel olarak anlamlı bir ilişki saptanmadı. Yalnızca lityum, yalnızca valproik asit veya yalnızca antipsikotik kullanan hastalar arasında stroop testinde ve WKET toplam yanlış sayısı dışında tüm alt kategorilerde istatistiksel olarak anlamlılık gösterecek düzeyde farklılık saptandı (p<0.05). İkili karşılaştırmalarda, yalnızca antipsikotik kullanan hastalarda stroop 1 toplam süresi ve stroop 3 toplam süresinin uzadığı; antipsikotik ve valproik asit kullanan hastalarda WKET tamamlanan kategori sayısında kontrol grubuna göre istatistiksel olarak anlamlılık gösterecek düzeyde daha az olduğu saptandı. Sonuç: Çalışmamızdan elde ettiğimiz bu bulgular, bipolar bozukluk tanılı hastalarda hücre içi sitokin, NfL ve OKB düzeylerinin sağlıklı kontrollerden daha yüksek olduğunu göstermektedir. Ayrıca bipolar bozukluk tanılı hastaların yürütücü işlevlerinde kontrol grubuna göre bozulma olduğu, IL6 ve IL-1β düzeylerinin bilişsel işlevlerde bozulma ile ilişkili olduğu belirlendi. Buradan yola çıkarak, ölçülen bu biyokimyasal parametrelerin düzeyi bipolar bozukluk tanısı alan hastaların bilişsel işlevlerini değerlendirmemiz konusunda yardımcı olabilir. Bu konuda daha geniş örneklemlerde, ileri çalışmaların yapılması gerekli olduğunu düşünmekteyiz. Anahtar Kelimeler: Bipolar Bozukluk, nöroinflamasyon, nörodejenerasyon, yürütücü işlevler
Keywords: MEDICINE; Psikiyatri